Optimal exercise modalities and doses for therapeutic management of osteoarthritis of the knee - Whitfield, Max; Tomlinson, Owen W. (Frontiers in Aging, 2025)
Osteoarthritis (OA) is a progressive osteoarticular disease affecting the whole joint. In the United Kingdom, OA is the most prevalent joint disease, with knee osteoarthritis (KOA) being the most common type of OA. Key symptoms of KOA include knee pain, stiffness, and loss of physical function. Different types of exercise can be performed in people with KOA, which exert different magnitudes of impact forces on the knee joint, whereby the National Institute for Health and Care Excellence (NICE) OA guidelines in fact recommend exercise as the core form of therapeutic OA management. However, the optimal type or dose – the cumulative intensity, duration, and frequency – of therapeutic exercise that most effectively provides KOA management is not currently known. This review aims to summarise and compare the literature, discussing optimal exercise modalities and doses for the management of KOA. All exercise modalities proved similarly beneficial at managing KOA with comparable improvements to knee pain, stiffness, and physical function, therefore with no optimal exercise modality identified. Benefits to KOA management was observed in everyone, including the elderly, obese, and those with severe KOA. Although, in those with severe KOA, walking was observed to only prevent further deterioration, rather than induce any symptomatic improvement. Furthermore, there was minimal difference between exercise modalities in relation to the improvements not only in KOA symptoms, but also modifiable KOA risk factors, adherence, adverse events, and QoL. Assessment of the dose-response relationship of each exercise modality showed that any dose of regular exercise was effective. Although, moderate intensity exercise performed three times weekly for 20-to-60-min appears optimal for KOA symptom control following most exercise modalities. Therefore, those with KOA should be encouraged to continue whatever exercise they currently do as should effectively manage symptoms, regardless of the modality or dose. However, those who do no exercise should use the present review in collaboration with clinicians via shared decision making to create a holistic exercise prescription. In summary, this review contributes to the literature through comprehensive discussion of different exercise modalities and doses in managing not only KOA symptoms, but modifiable KOA risk factors, exercise adherence, adverse events, and QoL. Additionally, summarised findings are discussed to give practical exercise recommendations to promote effective KOA management and recommendations for ongoing research.